Tax Payers Awareness in Nepal Regarding with Value Added Tax and Income Tax - Jitendra Prasad Upadhaya,; Paras Mani Acharya, (Pravaha, 2022)
This study analyzes the moral behavior of Nepalese taxpayers. Additionally, the study seeks to address the underlying reasons for non-compliance. Data were collected by 400 participant questioners and analyzed using thematic analysis. The result suggests that these taxpayers do not have sufficient technical knowledge and perceive the VAT system as complex. Tax knowledge and tax complexity are seen as contributing factors to taxpayer non-compliant behavior. Data is collected using a well-structured questionnaire. For analysis and interpretation, the researcher used the following statistical tools from her SPSS: Based on their analysis and interpretation, the researchers present important findings that the majority of consumers pay tax but are less aware of VAT. Consumers avoid paying tax in Nepal as VAT tends to be high.